Tinjauan Hukum Implementasi Mahar dalam Pernikahan - Fathoni, Muhammad Nur; Siti Wahyuni (Institut Agama Islam Negeri Metro, 2024)
This study aims to investigate investment dowries in marriage by focusing on their definition, legal aspects, and practical implementation, particularly in the context of Article 31 of the Compilation of Islamic Law (KHI). Utilizing methods of legal document analysis and literature review, the study examines the legal norms governing marriage and investment dowries as outlined in Article 31 of the KHI. The results of this study are expected to provide an in-depth understanding of the concept and legal provisions related to investment dowries in marriage, with a focus on the perspective of Article 31 of the KHI. By involving surveys of participants with experience or knowledge of investment dowry practices, the research also explores the practical implementation of such practices in society. This study contributes both conceptually and practically by detailing the legal perspectives contained in Article 31 of the KHI and providing insights into how the implementation of investment dowries can influence marital dynamics and family finances. Thus, this research not only delves into the legal aspects but also offers a practical understanding of how investment dowries are interpreted and implemented in societal life, particularly concerning the regulations within Article 31 of the KHI.